Stroke care during the COVID-19 pandemic: Case numbers, treatments, and mortality in two large German stroke registries - Brunssen, Alicia; Rücker, Viktoria; Heuschmann, Peter; Held, Jana; Hermanek, Peter; Berlis, Ansgar; Hecht, Martin; Berger, Klaus (Frontiers in Neurology, 2022)
Background and Purpose: At the beginning of the SARS-CoV-2 pandemic an alarming decline of hospitalizations for stroke was reported from several countries including Germany. We assessed hospitalization numbers and indicators of quality of stroke care in 2020 during pandemic containment measures. Materials and Methods: Data of two large German stroke registries for quality assurance were used. We included 395 hospitals with 467,931 documented cases in 2018-2020. Time interval between admission and thrombolysis, frequency of systemic thrombolysis and intra-arterial therapy (IAT), National Institutes of Health Stroke Scale (NIHSS) score on admission and in-hospital mortality were assessed. Changes in the second (Q2) and fourth (Q4) quarter 2020 were compared to corresponding quarters in 2019 by chi-squared tests. Results: Hospitalization numbers decreased in the two stroke registries by 8% and 10% in Q2 2020 and by 5% and 15% in Q4 2020 compared to the same quarters in 2019, respectively. The decline was particularly seen in women and patients with transient ischemic attack. In cases with cerebral infarction no increase in NIHSS scores on admission was observed and the proportion of patients with a time interval between admission and thrombolysis of ≤60 minutes was unchanged. No clear pattern was found in the frequency of systemic thrombolysis and IAT. In one of the registries in-hospital mortality of patients with cerebral infarction increased in Q2 2020 compared to the Q2 2019. Conclusions: Case numbers slightly decreased under pandemic conditions while our quarterly analysis indicated that quality of stroke care was largely unchanged throughout the year 2020.